Sasi local wisdom as a cultural capital for sustainable tourism development in Raja Ampat Regency, West Papua - Mentansan, George; Nauw, Monica; Awom, Rina; Ayorbaba, Musa; Lumi, Johnli; Reeve, David (Politeknik Negeri Bali, 2023)
This research aimed to describe the development of tourism in Raja Ampat, West Papua, Indonesia, which has entered its 19th year, which is developing and still exists with the support of local wisdom of coastal and island communities called sasi. This research was conducted by applying ethnographic methods and triangulation of field data to gather data on local wisdom of indigenous peoples in Raja Ampat. Results of the research showed that sasi as a form of practice for protecting and conserving marine natural resources has traditionally been carried out for generations in Raja Ampat, and has various local terms such as kalad/bu, kabus, and samson. Sasi local wisdom as the community's cultural capital has become the basis and strategic issue related to protecting the marine and coastal natural resources in supporting and maintaining.